2013
DOI: 10.4049/jimmunol.1300168
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell–Dependent In Vivo Generation of Autoregulatory T Cells by Antidiabetogenic MHC Class II

Abstract: Several mechanisms have been proposed to explain how certain MHC class II molecules afford dominant resistance to autoimmune diseases like type 1 diabetes (T1D). However, it remains unclear how protective MHC types can blunt autoreactive T cell responses directed against a diverse repertoire of autoantigenic epitopes presented by disease-promoting MHCs. In this study, we show that expression of I-E on dendritic cells (DCs) of NOD mice promotes the differentiation of MHC promiscuous autoreactive CD4+ clonotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 66 publications
3
27
0
Order By: Relevance
“…Exposure to increased antigenic loads and/or differentially processed epitopes in the periphery (41) could then suffice to fuel the activation of these thymic escapees and their recruitment into an autoimmune response. Our studies with the diabetogenic, MHC-promiscuous (but I-A g7 -restricted) 4.1-TCR are entirely compatible with this view (3436, 38, 39). …”
Section: Mhc Polymorphism and Positive/negative Selectionsupporting
confidence: 86%
See 1 more Smart Citation
“…Exposure to increased antigenic loads and/or differentially processed epitopes in the periphery (41) could then suffice to fuel the activation of these thymic escapees and their recruitment into an autoimmune response. Our studies with the diabetogenic, MHC-promiscuous (but I-A g7 -restricted) 4.1-TCR are entirely compatible with this view (3436, 38, 39). …”
Section: Mhc Polymorphism and Positive/negative Selectionsupporting
confidence: 86%
“…The latter observations brought forth the idea that protective class II polymorphisms located at or near the peptide-binding groove may be recognized by certain MHC-promiscuous autoreactive TCRs with an avidity and/or affinity above the threshold required for negative selection. We have recently shown that dendritic cells play a key role in this process (38, 39). Figure 1 depicts the proposed relationship between pMHC:TCR interaction strength and its outcome in terms of the selection of pathogenic vs. regulatory T cell clonotypes, and how MHC polymorphisms play into this selective process.…”
Section: Mhc Polymorphism and Positive/negative Selectionmentioning
confidence: 99%
“…The notion of an intestinal impact on the development of T1D is supported by studies in humans and mice, and is often referred to as the "leaky gut hypothesis" (37). In support of a role for the E complex working via such mechanisms, cell transfer experiments indicated that protection is mediated by the Eexpressing macrophage or dendritic cell lineage (13), which is supported by genetic ablation studies showing a requirement for E-expression on the CD11c + but not CD19 + cell lineage (12). Our observation of increased T reg cell proportions in the cecum of Eα16/NOD mice could represent an effect of early-life microbial stimulation on CD11c…”
Section: Discussionmentioning
confidence: 95%
“…A second model argued for altered autoantigen presentation in E-expressing NOD mice: the E complex would outcompete A g7 for limited pathogenic peptides. This mechanism also proved unlikely because E + and E − antigenpresenting cells (APCs) from NOD mice similarly present peptide to and prime autoreactive T cells in vitro and in vivo (11,12). A third proposed mechanism, that E complex expression alters the cytokine skewing of CD4 + T effector cells or promotes the generation of Foxp3 + T regulatory (T reg ) cells, has been supported by data from some studies (5) but refuted by results from others (13).…”
mentioning
confidence: 99%
“…Homeostasis of DCs was shown to play a critical role in autoimmune damage of pancreatic islets (Dissanayake et al, 2011). In the standard NOD model of autoimmune diabetes, as well as in the BDC2.5 TCR-transgenic model, the role of DCs in initiating autoimmune diseases and their potential in tolerogenic therapies have been clearly demonstrated (Turley et al, 2003;Tarbell et al, 2007;Mukhopadhaya et al, 2008;Driver et al, 2010;Tsai et al, 2013). We believe that the visual evidence of direct T reg -T eff interaction in target tissue in vivo, with or without the involvement of CD11c + DCs, reconciles the discrepancy between in vitro and in vivo observations on a basic aspect of T reg cell biology.…”
Section: Ar Ticlementioning
confidence: 99%